Hyperacute Liver Failure with Multi-organ Dysfunction Syndrome (MODS) by Leptospirosis: A Case Report - Tripathi, Nilay; Rajpal, Naresh; Jain, Gaurav; Katiyar, Prashant (Indian Journal of Community Health, 2023)
Introduction: Leptospirosis may have multi-organ involvement in its severe form with potentially life-threatening consequences. However, acute fulminant hepatic failure is very uncommonly reported. A case study is presented here with fulminant hepatic failure and a diagnostic dilemma for etiology. Case history: A 40-year-old man with no significant medical history presented with fever, muscle pain, weakness, and pain in the upper abdomen. On clinical work, he has developed multi-organ hepatic, respiratory, and renal failure. A timely workup was done, but due to the rapid progression of the disease, the patient succumbed to the disease in the intensive care unit by the time his report for positive leptospirosis test arrived. Conclusion: Leptospirosis must be considered as an important differential diagnosis of acute liver failure patients. An early suspicion for leptospirosis in patients with fulminant hepatic failure and multi-organ failure in India particularly in the rainy season is warranted owing to its high mortality rate.